Oxytocin Massage Stramlining Breast Milk: Literature Riview - Sri Wahyuningsih; Nurul Hayati; Musviro; Riska Agustina (Nursing and Health Sciences Journal (NHSJ), 2022)
Oxytocin massage is massage or stimulation of the spine to release oxytocin, causing the breasts to release milk. With oxytocin massage, the mother will feel calm, relaxed, reduce pain, and love her baby, so with this the hormone oxytocin and water Mother's milk comes out quickly. The implementation of oxytocin massage therapy must be carried out effectively in order to get maximum results. Aim of this study was to identify the effectiveness of oxytocin massage therapy on increasing breast milk production in the postpartum period. This study uses a literature review using the PRISMA checklist protocol and evaluation. Search articles using two databases, namely PubMed and Scholar. The oxytocin massage intervention was effective for postpartum maternal patients on the first to third day who had not expelled colostrum or had impaired breast milk production. Oxytocin massage is effective if done twice a day with a duration of 3-5 minutes or for approximately 2-3 minutes with 2-3 massages. The implementation of oxytocin massage therapy can affect the release of colostrum in postpartum mothers. There is a need for development in other studies, including combining oxytocin massage with other non-pharmacological methods in order to further support the increase in breast milk production in the postpartum period.